Brothels, depravity and abandoned women: illegal sex in antebellum New Orleans - Schafer, Judith Kelleher (Louisiana State University Press, 2009)
Selling sex and the law -- "Disgusting depravity" : sex across the color line -- The sexual exploitation of children -- Infamous public women -- Larceny and robbery among prostitutes -- Violent lives -- The murder of a "lewd and abandoned woman" : state of Louisiana v. Abraham Parker -- Keeping a brothel in antebellum New Orleans -- "An ordinance concerning lewd and abandoned women."